PHILOSOPHY OF IDENTITY AND EXTENTIONAL MOTIVATION IN EASTERN AND WESTERN LITERARY DIALOGUE: PHILOSOPHICAL-LINGUISTIC REFLECTION OF HUMAN PURPOSE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This scientific article is aimed at a comparative analysis of the sociolinguistic-philosophical issues of studying how Eastern and Western scholars express their ideas about identity, existence and the purpose of life through motivational language from the perspective of motivational discourse. It is revealed that in the works of Alisher Navoi, Jalaluddin Rumi, Ralph Waldo Emerson and Victor Frankl, language serves as a methodology of philosophical reflection for people to determine the meaning and moral direction of life and motivational language in socio-philosophical, artistic and creative literature not only inspires readers, but also encourages them to master the necessary idea to understand what they need to understand in order to become useful people for society in the future, and that in finding a solution to this problem, Eastern literature often focuses on unity, spirituality and harmony with the divine, while Western literature emphasizes personal freedom, individuality and moral choice. Therefore, it is possible to conclude that language in literature, through words with deep philosophical meanings, turns into a place of philosophical reflection that both describes and shapes human existence.